2024
DOI: 10.1083/jcb.202301090
|View full text |Cite
|
Sign up to set email alerts
|

STK19 is a DNA/RNA-binding protein critical for DNA damage repair and cell proliferation

Yuling Li,
Yanqiu Gong,
Yue Zhou
et al.

Abstract: STK19 was originally identified as a manganese-dependent serine/threonine-specific protein kinase, but its function has been highly debated. Here, the crystal structure of STK19 revealed that it does not contain a kinase domain, but three intimately packed winged helix (WH) domains. The third WH domain mediated homodimerization and double-stranded DNA binding, both being important for its nuclear localization. STK19 participated in the nucleotide excision repair (NER) and mismatch repair (MMR) pathways by recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
3
4
2
Order By: Relevance
“…1 e). This is different from the conclusion of the recent paper 17 . The latter emphasized more about the capability of STK19 to form dimers, especially in the presence of DNA, which is still possible.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…1 e). This is different from the conclusion of the recent paper 17 . The latter emphasized more about the capability of STK19 to form dimers, especially in the presence of DNA, which is still possible.…”
Section: Resultscontrasting
confidence: 99%
“…In the absence of a kinase domain, the current official protein and gene names of STK19 need to be changed to better reflect its identity. The same conclusion was achieved by another two independent studies 10 , 17 .
Figure 1 Overall structure of the human STK19 protein.
…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Based on limited sequence similarity to a tyrosine kinase and in vitro assays showing kinase activity to serine/threonine residues it was named STK19 [37][38][39] . However, recent data showed that the originally proposed 41 kDa STK19 form 36 was not expressed, but that the main STK19 gene product is 110 amino acid shorter and forms a 29 kDa protein that does not have detectable kinase activity 40,41 , resulting in its current nomenclature as "Inactive serine/threonine-protein kinase 19". STK19 was thus far mainly studied as it contained recurrent UV-induced melanoma driver mutations [42][43][44] .…”
Section: Introductionmentioning
confidence: 99%
“…STK19 was thus far mainly studied as it contained recurrent UV-induced melanoma driver mutations [42][43][44] . However, the functional consequence of the recurrent STK19 D89N mutation is controversial, as this mutation is not present in the coding region of the 29 kDa STK19 form 40,41,43 . Interestingly, recently a role for STK19 during the cellular response to transcription-blocking lesions (TBLs) has been suggested 28,41,45,46 .…”
Section: Introductionmentioning
confidence: 99%